Perbedaan Antigen pada Golongan Darah Bombay dan Parabombay: Tinjauan Sistematik - Cityta Putri Kwarta; Maifa Tri Wulandai (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background: Bombay and Para-Bombay blood groups are rare blood types characterised by the absence of H antigen on the surface of red blood cells. This condition has a significant impact on diagnosis and blood transfusion, as individuals with these blood types can only receive donors with the same blood type. Methods: This study conducted a literature review by searching articles in databases such as PubMed, Google Scholar, and SciELO. The selected articles included the last five years of original research on Bombay and Para-Bombay blood groups, antigenic differences, as well as their clinical implications. Results: Bombay blood group lacks FUT1 enzyme activity, hence H, A and B antigens are not formed. In contrast, the Para-Bombay blood group has very low FUT1 activity, producing few A or B antigens. The Bombay phenotype is often mistaken for blood group O, despite having anti-H antibodies, which can trigger acute haemolytic transfusion reactions. Specialised testing, such as anti-H lectin, is important to ensure blood compatibility. Further research on FUT1 gene variations may deepen molecular understanding and support clinical management of patients. Conclusion: Bombay and Para-Bombay blood groups require special attention in diagnosis and transfusion. Better antigenic understanding and appropriate diagnostic techniques may prevent fatal complications and improve transfusion therapy.